Epstein–Barr Virus Latent Membrane Protein-1 (EBV LMP-1) in Nasopharyngeal Carcinoma: Immune Correlates and Potential as A Clinical Outcome Biomarker - Fachiroh, Jajah; Ramadhani, Fitriya; Hertanto, Nayaka Bagus Wahyu Agung; Paramita, Dewi Kartikawati (The Indonesian Biomedical Journal, 2026)
In endemic populations, nasopharyngeal carcinoma (NPC) is associated with epstein-barr virus (EBV) infection, with latent membrane-1 (LMP-1) playing a major role as an oncoprotein. Despite this well-established biological role, the clinical use of LMP-1 remains limited; therefore this review aimed to discuss the potential use of LMP-1 as clinical biomarker. Based on systematic searching results in two major biomedical journal databases, in this review, only a small number of studies that evaluated LMP-1 as a clinical outcome. Studies examining the relationship between LMP-1 and its related biomarkers in clinical samples were particularly scarce. By mapping the existing literature, this scoping review highlights mechanistic linking of LMP-1 to specific biomarker, such as interferon gamma (IFN-γ), leukemia inhibitory factor (LIF), chemokine (C-X-C motif) ligand 9 (CXCL9), programmed cell death ligand-1 (PDL-1), and had a positive regulatory loop with EBV-encoded small RNA (EBERs) serving to amplify inflammatory signals that facilitates NPC progression. A clear gap between evidence mechanism of LMP-1 and clinical research practice was observed. This may related to several reasons, including low detectability, a heterogeneous expression in tumor tissue; hence shifted into surrogated biomarkers that reflected LMP-1 signalling than the protein itself. Future studies should focus on combining LMP-1 with related inflammatory or immune markers, and conducting well-designed clinical studies to better define the potential role of LMP-1 within clinically relevant biomarker strategies for NPC.KEYWORDS: oncoprotein, stage, malignancy of nasopharynx, prognosis, survival, inflammation